(untitled) (Vietnam Journal of Community Medicine, 2023)
Purposes: Describe the outcomes of knowledge and attitude about infection control in Hanoi Medical University Hospital in 2021. Methods: A cross-sectional study, 210 nurses participating in the study, using a nursing proportional sampling method in 11 departments. Results and conclusion: Among 210 nurses working at Hanoi Medical University Hospital participating in the study were 77.6% female and 22.4% male, the average age of the study subjects was 31.4 ± 4.8. The rate of nurses knowing bacteriophage is 52.4%. The rate of nurses having a positive attitude about preventing hospital-acquired infections is 97.6%. Factors related to nursing knowledge: age (OR=2,6, 95% CI: 1,5 - 4,8, p=0,001) and working seniority (OR=1,8, 95% CI: 1,1 - 3,0, p=0,009).